Схемотехническое моделирование и синтез активных СВЧ-фильтров на полевых транзисторах Шоттки - Filinyuk, N. А.; Kuzemko, А. М. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Existing mathematical models of Schottky field-effect transistors are analyzed. Studies were conducted on the dependence of the invariant stability coefficient for three transistor connection schemes, as well as on the output resistance of the common-drain circuit with inductive and active resistance connected at the input. Schemes of active microwave filters suitable for implementation as hybrid or semiconductor integrated circuits have been developed.